Planning and Measuring the Effects of Intervention and Rehabilitation after Right Middle Cerebral Artery Infarction - A Case Analysis - Manrai, Mishi (My University, 2018)
The present work is a case study of a patient who suffered Right Middle Cerebral Artery Infarction and as a result suffered a stroke. Subsequently he underwent two surgeries, right decompressive craniotomy and Right FTP autologus bone flap cranioplasty. After this, the patient was diagnosed with Global Aphasia. He had severe language disability as well as his left side of the body was paralyzed. On 5th July, 2017 his global aphasia impairment level was 42%. Also, it was observed that the patient was suffering from severe left hemi-neglect. Cognitive Language Therapy, Visual Scanning Training and some additional techniques were practiced for intervention and rehabilitation of the patient. This resulted in the improvement of various aspects of language functionality of the patient. By 17th April the global aphasia impairment quotient had come down to 26% with maximum improvement in Visual and Reading Problems and Perceptuo Motor Problems. The left hemi-neglect had also come down significantly. This work covers the various strategies and techniques used for improving the language functioning of the patient. Also it discusses the future path to be taken for improvement in those aspects of language functioning which did not show much improvement by earlier treatment strategy.
Keywords: Infarction; global aphasia; cognitive language therapy; hemi-neglect; Rehabilitation